Comparative Efficacy of Medical Treatments for Thyroid Eye Disease: A Network Meta-Analysis - Nuo Xu; Yi Cui; Tianlu Xie; Mi Zheng (Journal of Ophthalmology)
Purpose. Numerous medical strategies have been proposed for the treatment of thyroid eye disease (TED); however, the best methods for standard treatment are still a matter of controversy. The purpose of this network meta-analysis was to integrate previous evidence to create hierarchies of comparative efficacy of eleven commonly used medical treatments for TED. Methods. A comprehensive search of electronic scientific literature databases was performed and the data from randomized controlled trials (RCTs) comparing treatment outcomes for patients with active TED were selected. Treatment strategies included in this network meta-analysis were intravenous glucocorticoids (IVGC), oral glucocorticoids (OGC), orbital injection of glucocorticoids (OIGC), orbital radiotherapy (OR), intravenous glucocorticoids combined with orbital radiotherapy (IVGC + OR), oral glucocorticoids combined with orbital radiotherapy (OGC + OR), rituximab (RTX), somatostatin analogs, intravenous immunoglobulin (IVIG), teprotumumab, and cyclosporine. The outcomes were response rate, mean difference in proptosis reduction, and reduction in disease activity. A random-effects network meta-analysis using a frequent method was conducted in STATA. Results. Twenty-three studies comprising a total of 1047 patients were included in the analysis. Inconsistency plots showed heterogeneity in the IVGC-Placebo-RTX loop to some extent (RoR = 8.029, P=0.075). Rankings of response rates were as follows: IVGC + OR, teprotumumab, IVGC, OGC + OR, RTX, OIGC, OR, IVIG, OGC, somatostatin, placebo, and cyclosporine. The rank probability analysis of proptosis reduction showed that teprotumumab was the most effective, followed by IVGC, IVGC + OR, OIGC, OGC, OGC + OR, OR, somatostatin, cyclosporine, and placebo. Conclusions. IVGC, alone or combination with OR, and teprotumumab should be preferred as the most effective strategies for active moderate to severe TED. Teprotumumab showed profound effect on proptosis reduction. OIGC, OR, and somatostatin analogs showed some statistical benefit and can be employed as second-line treatment strategies. RTX is a promising biologic agent, but more RCTs are required to define its appropriate role in treating TED.